Animal Models for COVID-19: Hamsters, Mouse, Ferret, Mink, Tree Shrew, and Non-human Primates - Shou, Shuyu; Liu, Menghui; Yang, Yang; Kang, Ning; Song, Yingying; Tan, Dan; Liu, Nannan; Wang, Feifei; Liu, Jing; Xie, Youhua (Frontiers in Microbiology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel coronavirus causing acute respiratory tract infection in humans. The virus has the characteristics of rapid transmission, long incubation period and strong pathogenicity, and has spread all over the world. Therefore, it is of great significance to select appropriate animal models for antiviral drug development and therapeutic effect evaluation. Here, we review and compare the current animal models of SARS-CoV-2.